Formulation of a Combination of Moringa oleifera Leaves and Monopterus albus Eel as a Functional Food Diversification for the Stunting Prevention - Woro Tri Utami; Wiqodatul Ummah (Universitas Tribhuwana Tunggadewi, 2025)
Stunting remains a threat to Indonesia's future generations. Local plants with high nutritional content include moringa leaves. This study aims to determine the level of acceptance of the subjects toward the combination of moringa leaves and eel sausage formulation and to assess the effectiveness of the sausage formulation in improving the weight and height of infants. This study uses an experimental method involving 30 toddlers, with subjects taken using purposive sampling. This study was divided into a treatment group and a control group. The study subjects consisted of 30 toddlers (15 toddlers in the treatment group and 15 toddlers in the control group). Data analysis included organoleptic testing to measure subjects' preference for the sausage formulation and a Paired-sample t-test to assess the formulation's effectiveness in improving weight and height. The results of the study showed that the average level of preference of mothers of toddlers during the organoleptic test of moringa leaves and eel sausage in terms of aroma and taste was rated as very good, while the criteria of color and texture were rated as good. There was an increase in the weight of infants before and after being given moringa leaves and eel sausage. The average weight of toddlers before being given moringa leaves and eel sausage was 15.33 kg and after being given moringa leaves and eel sausage, the average weight of toddlers increased by 0.48 kg to 15.81 kg. Meanwhile, the average height of toddlers before being given moringa leaves and eel sausage was 102.07 cm and after being given moringa leaves and eel sausage, the average height of toddlers increased by 0.6 cm to 102.67 cm. The conclusion of the study confirms that the formulation of moringa leaves and eel sausage has the potential to positively impact the increase in toddler weight.